1989
DOI: 10.1002/mrd.1080010305
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence and pattern of expression of the sea urchin (Paracentrotus lividus) α‐tubulin genes

Abstract: To study the molecular aspects of the regulation of transcription of a multigene family, we have isolated and sequenced cDNA and genomic clones coding for the alpha-tubulin of the sea urchin Paracentrotus lividus. Two cDNA clones, P alpha 10 and P alpha 4, contain respectively the coding information for 391 C-terminal and for 338 N-terminal amino acids of the 452 residues that constitute the complete protein. They show silent nucleotide substitutions only, suggesting that P alpha 10 and P alpha 4 represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(42 reference statements)
3
10
0
Order By: Relevance
“…2C) with a peak of acetylation at 24 hrs of development. This dynamics of the PTMs is in agreement with the expression profile of the PlTalpha2 tubulin gene during development, in fact the alpha2 transcript appears only from blastula stage (about 15 hrs of development), accumulating during late developmental stages (Gianguzza et al, 1989).…”
Section: Post Translational Modifications (Ptms) and Pltalpha2 Gene Asupporting
confidence: 85%
See 4 more Smart Citations
“…2C) with a peak of acetylation at 24 hrs of development. This dynamics of the PTMs is in agreement with the expression profile of the PlTalpha2 tubulin gene during development, in fact the alpha2 transcript appears only from blastula stage (about 15 hrs of development), accumulating during late developmental stages (Gianguzza et al, 1989).…”
Section: Post Translational Modifications (Ptms) and Pltalpha2 Gene Asupporting
confidence: 85%
“…We found that specific histone modifications (H3K9Ac, H3K-4me3), which induce an accessible chromatin conformation, occur dynamically at level of core promoter in the same developmental window previously highlighted as the temporal interval in which the PlTalpha2 neural gene is expressed (Gianguzza et al, 1989;Gianguzza et al, 1995).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations